Targeting poverty through community-based public works programs: experience from South Africa - Adato, Michelle; Haddad, Lawrence J. (Informa UK Limited, 2002)
Since the transition to democracy, South African public works programs are to involve community participation, and be targeted to the poor and women. This paper examines the targeting performance of seven programs in Western Cape Province, and analyzes the role of government, community-based organizations, trade unions, and the